fourier_transform_Gaussian

fourier_transform_Gaussian - -ln G(0 = 2 2 2(9 Since the...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Fourier Transform of the Gaussian Konstantinos G. Derpanis October 20, 2005 In this note we consider the Fourier transform 1 of the Gaussian. The Gaussian function, g ( x ), is defined as, g ( x ) = 1 σ 2 π e - x 2 2 σ 2 , (3) where R -∞ g ( x ) dx = 1 (i.e., normalized). The Fourier transform of the Gaussian function is given by: G ( ω ) = e - ω 2 σ 2 2 . (4) Proof : We begin with differentiating the Gaussian function: dg ( x ) dx = - x σ 2 g ( x ) (5) Next, applying the Fourier transform to both sides of ( 5 ) yields, iωG ( ω ) = 1 2 dG ( ω ) (6) dG ( ω ) G ( ω ) = - ωσ 2 . (7) Integrating both sides of ( 7 ) yields, ω Z 0 dG ( ω 0 ) 0 G ( ω 0 ) 0 = - ω Z 0 ω 0 σ 2 0 (8) ln G ( ω )
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: -ln G (0) = 2 2 2 . (9) Since the Gaussian is normalized, the DC component G (0) = 0, thus ( 9 ) can be rewritten as, ln G ( ) =- 2 2 2 (10) Finally, applying the exponent to each side yields, e ln G ( ) = e- 2 2 2 (11) G ( ) = e- 2 2 2 (12) as desired. 1 The Fourier transform pair is given by: F ( ) = Z- f ( x ) e-ix dx (1) f ( x ) = 1 2 Z- F ( ) e ix d, (2) where i denotes the complex unit. 1...
View Full Document

This note was uploaded on 02/04/2012 for the course COMPUTER 101 taught by Professor Ahmed during the Spring '11 term at alamo.edu.

Ask a homework question - tutors are online